Research on Tai Chi teaching during epidemic prevention and control - Wen, Dean (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: To improve the physical fitness of the masses, better enhance the body's immunity, and fight against the epidemic through studying the methods of exercising Tai Chi during the epidemic period, summarizing and promoting the application. 56 students from the Tai Chi class of Huaiji College, Guangdong University for the Senior. Among them, 10 were males, 46 were females. 24 were 45-55 years old, and 32 were 56-65 years old. There are 30 employees and 26 retired and unemployed. Research content: Tai Chi exercise methods during epidemic prevention and control period. Methods: 1. Comply with the general requirements for epidemic prevention. Participants are required to respond to the government's call to maintain good hygiene, wash hands frequently, wear masks when going out, and be separated by one meter and so on which all belong to general epidemic prevention requirements. 2. Carry out the activity of “Practice Tai Chi at Home to Strengthen the Body to Fight the Epidemic”. On January 23, 2021, our college issued a notice to the students to stay at home as much as possible, reduce going out, and avoid the risk of cross-infection. The students in the Tai Chi class were required to cancel the group practice every morning and exercised it at home persistently instead. Our college rewarded activists who "practice Tai Chi at home to strengthen the body against the epidemic". 3. Carry out online teaching and classes are not suspended as a result. Our college mainly used WeChat groups and Dingding software or "Rain Class" for teaching, drills and demonstrations. The courses included "Eight Methods and Five Steps", "24 Simplified Tai Chi", " Tai Chi with Seven Stars and Eighteen Forms ", and other video content collected on the Internet was also pushed to the students’ QQ group for self-study. 4. Carry out the teaching of " Tai Chi with Seven Stars and Eighteen Forms ". In October 2020, the epidemic was basically under control, and when the school can have classes as usual, our college invited Zhaoqing City Tai Chi Association to teach " Tai Chi with Seven Stars and Eighteen Forms ". " Tai Chi with Seven Stars and Eighteen Forms " is created by a master of Beijing martial arts--Mr. Huo Dongli. Based on his decades of martial arts experience and teaching experience, he combines humanistic and geographic characteristics in Zhaoqing city as well as the essence of different types of Tai Chi and Eight Trigram Palm. It has rich connotation and every move and step is stretching and generous, rigid and flexible, and has a unique effect on enhancing immunity, especially suitable for practice during the epidemic. 5. Participate in social sports instructor training. Seven key trainees were selected to participate in the Tai Chi Social Sports Instructor Training held by the Bureau of Culture, Sports, Tourism and Sports of Zhaoqing City, Guangdong Province in 2020. They passed the training and assessment, obtained the social sports instructor certificate, and provided scientific and legal talent support for the development of mass sports activities in our county. These instructors took up their posts with certificates and were active in teaching Tai Chi in our county's agencies, schools, communities, parks and other places, and had made great contributions to our county's nationwide fitness fight against the epidemic. They felt that their work had a sense of accomplishment, which drove the enthusiasm of the whole class to learn Tai Chi. 6. Organize public welfare training courses. Hold 24 forms of simplified Tai Chi. The 24-style simplified Tai Chi has concise content and standardized movements, which fully reflects the sports characteristics of Tai Chi and is of great help in improving immunity. During the epidemic, Tai Chi was declared by officials of the National Health Commission to walk into the wards and shelter hospitals in the epidemic area and step onto the battlefield of fighting the epidemic. This was an unprecedented pioneering move and became a bright spot in the fight against the epidemic. The 24-style simplified Tai Chi public welfare training class is well received by the students, people enrolled enthusiastically, and the learning enthusiasm is increasing continuously. 7. Actively organize students to participate in various Tai Chi competitions to promote learning. Our college organized students to participate in the first "Exercising Martial Arts Conference" of Guangdong Province in 2020, and won two gold medals and one silver medal. Four students participated in “Guangdong Martial Arts Routine Championship 2020” and won two gold medals, two silver medals and two bronze medals. Two members of Tai Chi team participated in the " Guangdong Martial Arts Cup" Global Tai Chi Network Competition (Guangdong Station) and won two silver medals. The whole class participated in the 2nd Huaiji County Workers Tai Chi Competition and won the collective first prize. Two students participated Huaiji County's "National Fitness, Fighting the Epidemic" Kung Fu Master Short Video Contest and won two gold medals. Through competitions to promote learning, the students’ interest and enthusiasm for learning Tai Chi has been further increased. 8. Participate in the "2021 Huaiji County Online Spring Festival Gala". Due to the epidemic, the 2021 Spring Festival Gala in Huaiji County did not organize live viewing, instead, it was broadcast online. Our college organized a program "Health Qigong(an ancient Chinese exercise that focuses on breathing)—Qi Dance" organized by Tai Chi class students to sign up for the online Spring Festival Gala in Huaiji County. And with their efforts, it was successfully passed the preliminary contest and entered the final show of the Huaiji Spring Festival Gala. "Health Qigong-Qi Dance" is adapted from the mixed movements of Health Qigong "Great Dance", "Ba Duan Jin (an independent and complete set of fitness exercises)", "Mawangdui Guiding Technique" and "Yi Jin Jing (a Qigong exercise passed down from ancient times)" promoted by the State Sports General Administration. The movements are simple and easy to learn, and can effectively improve the body's immunity. It is a way to have a healthy and civilized holiday which can be promoted to the masses during the epidemic, and also a way to promote effective epidemic prevention methods for home fitness. The dance is beautiful, the costumes are gorgeous, the arrangement is exquisite with the music of "Sky Boundary", the love story is interpreted in the form of Health Qigong, and the stage background is beautiful which make the dance highly artistic, ornamental and practical. This program was deeply loved by the audience, and the number of online votes ranked third in the entire program. It played a certain role in promoting fitness exercises and improving the physical fitness of the masses during the epidemic. Results: Practice has proved that through the above-mentioned various methods, as well as the unremitting exercise of Tai Chi, the trainees can strengthen the immunity and fight against the epidemic, be healthy and live a happy life. Among the students in this class, 6 had their high blood pressure returned to normal, 7 had a good sleep state, 24 had a marked improvement in their mental state, and other improvements. Conclusion: 1. Activate the self-repair system and improve immunity. Practicing Tai Chi can greatly increase the amount of oxygen inhaled, which can enliven the blood, open up the body meridians, promote the body's metabolism, activate the body's repair function, and enhance the body's immunity. 2. Dredge the meridians and make the body and mind peaceful. Tai Chi uses Qi to move the body. In practice, there are often numb fingertips, faint ringing of joints, acupuncture, abdominal ringing, etc. These are normal responses to the smooth flow of meridians. The channels and collaterals are unblocked, the blood is cleared, and the fatigue is eliminated. 3. Relax the nervous system. Tai Chi is practiced in the calm and natural environment, concentrating and gathering energy, calming and comfortable, so that the cranial nerves can be fully rested, the nervous system can be relaxed, dizziness can be relieved, mental illness can be avoided and blood pressure can be regulated. Tai Chi is a kind of exercise in which there is movement in stillness, and there is stillness in movement. There are Yin and Yang, which conforms to the law of human movement. It helps the brain release more happy hormones, which can make people feel happy and prolong life. 4. Enhance heart function and prevent myocardial infarction. Practicing Tai Chi can stimulate blood all over the body, enhance heart function, make the heart slowly and powerfully reduce the formation of blood clots, and reduce the possibility of myocardial infarction. 5. Strengthen blood vessels and improve blood circulation. Tai Chi requires the body and limbs to move spirally, softly and continuously, which can increase the elasticity of blood vessels, reduce the possibility of blood vessel rupture, and can also enhance the elasticity of the whole body, and enhance the blood circulation and metabolism of the body. 6. Prolong life, open up wisdom and increase wisdom. Tai Chi is a kind of exercise in which there is movement in stillness, and there is stillness in movement. There are Yin and Yang, which conforms to the law of human movement. It helps the brain release more happy hormones, feels happy, and prolongs life.